Kids finder through bluetooth technology - Yusof A.M.; Rusli M.E.; Yusof Y. (IEEE Computer Society, 2023)
A statistic on children been kidnapped or been lured away by strangers is continuously increased. There is no safer place for kids. For parents or guardians, taking care of their children is not an easy task. Until now, a few wireless or mobile devices based on GPS, Wi-Fi and radio frequency are available in the market enabling the parent to monitor child's whereabouts. Each technology is categorized based on cost, durability and accuracy. However, the usage of Bluetooth is not been explored. Wireless kids finder based on Bluetooth technology can be another good alternative that are cheap and effective. In this paper, the comparison between the proposed Bluetooth based technology with current products and method of detecting are elaborate in detail. IEEE.